Functional Cognitive Disorder: Differential Diagnosis of Common Clinical Presentations. (28th April 2022) - Kemp, Steven; Kapur, Narinder; Graham, Christopher D; Reuber, Markus
Abstract: Background: Cognitive symptoms in the absence of neurological disease are common. Functional cognitive disorder (FCD) has been conceptualized as a cognitive subtype of functional neurological disorder. Although FCD is understood as different from exaggerated or feigned cognitive complaints, previous accounts have provided little practical advice on how FCD can be separated from factitious or malingered cognitive complaints. Also, the distinction of FCD from other medical or mental health disorders that impact on cognition is an area of ongoing study and debate. Diagnostic precision is important to prevent iatrogenesis and for the development of needed treatment protocols. Method: We summarize the current literature and present seven anonymized case vignettes to characterize the challenges in this area and develop proposals for solutions. Results/Conclusions: Recognizing the limitations of categorical diagnostic systems, we position FCD as distinct from feigning and cognitive symptoms of psychiatric disorders, although with overlapping features. We set out typical clinical features and neuropsychological profiles for each category of cognitive disorder and a statistical method to analyze performance validity tests/effort tests to assist in determining feigned or invalid responding.